1998
DOI: 10.1128/jvi.72.8.6339-6347.1998
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Components Interact with Adenovirus Type 5 Minimal DNA Packaging Domains

Abstract: Adenovirus type 5 DNA packaging is initiated from the left end of the viral genome and depends on the presence of acis-acting packaging domain located between nucleotides 194 and 380. Multiple redundant packaging elements (termed A repeats I through VII [AI through AVII]) are contained within this domain and display differential abilities to support DNA packaging in vivo. The functionally most important repeats, AI, AII, AV, and AVI, follow a bipartite consensus motif exhibiting AT-rich and CG-rich core sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 37 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…Ad DNA is packaged in a polar fashion starting at the left end of the genome [Daniell, 1976; Tibbetts, 1977; Hammarskjold and Winberg, 1980; Hearing et al, 1987]. Extensive analyses of the Ad5 genome have shown that there is a domain between left end nucleotides 200 and 400 that is absolutely required for encapsidation of viral DNA [Hearing et al, 1987; Grable and Hearing, 1990; Grable and Hearing, 1992; Schmid and Hearing, 1997, 1998, 1999; Sandig et al, 2000; Ostapchuk and Hearing, 2003b]. This domain can function at the right end of the genome as well, and recombinant genomes carrying packaging domains at both ends of the genome are viable [Hearing and Shenk, 1983; Parks and Graham, 1997].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Ad DNA is packaged in a polar fashion starting at the left end of the genome [Daniell, 1976; Tibbetts, 1977; Hammarskjold and Winberg, 1980; Hearing et al, 1987]. Extensive analyses of the Ad5 genome have shown that there is a domain between left end nucleotides 200 and 400 that is absolutely required for encapsidation of viral DNA [Hearing et al, 1987; Grable and Hearing, 1990; Grable and Hearing, 1992; Schmid and Hearing, 1997, 1998, 1999; Sandig et al, 2000; Ostapchuk and Hearing, 2003b]. This domain can function at the right end of the genome as well, and recombinant genomes carrying packaging domains at both ends of the genome are viable [Hearing and Shenk, 1983; Parks and Graham, 1997].…”
mentioning
confidence: 99%
“…Synthetic packaging A repeats were inserted into the Ad5 genome in place of the authentic packaging domain [Schmid and Hearing, 1998]. Viruses with WT or very close to wild type levels of packaging were recovered that contained: (1) a dimerized pair of A repeats 1 and 2; (2) dimeric copies of A repeats 5, 6, and 7; or (3) six tandem copies of A repeat 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For the xenogenic mastadenoviruses there are three ORFs at the left end that show homology with HAdVs [77][78][79][80]. The genome packaging signal is also present within the first ^500 nucleotides of the HAdV5 genome [81], but until recently this had not been defined for any xenogenic virus. For CAdV2, however, it was shown that the packaging region consists of a ^200bp region that contains redundant, but not functionally equivalent sequences.…”
Section: Left End Sequencesmentioning
confidence: 99%
“…For CAdV2, however, it was shown that the packaging region consists of a ^200bp region that contains redundant, but not functionally equivalent sequences. The consensus sequence for HAdVs [81] is present only once and is of minor importance [82].…”
Section: Left End Sequencesmentioning
confidence: 99%